CFD Simulation of Two-Phase Separation in a Liquid Flash Drum - Ang , Yee Ying (IRC, 2016)
The performance of a two-phase separator is critical to oil and gas production companies. Liquid flash drum is used as a two-phase separator in oil and gas plants to separate homogeneous hydrocarbon mixtures. The purpose of this study is to determine the separation efficiency of a liquid flash drum and investigate the effects of changing inlet diameters on separation efficiency. CFD simulation of oil and gas separation is performed on a liquid flash drum under steady-state conditions. Two-dimensional CFD model of a liquid flash drum is created and meshed using the ANSYS ICEM CFD 15.0 commercial software. Grid dependency test is performed to validate the numerical results.